Plastic Jali-Jali Rope Weaving Techniques Mangosteen Fruit Profits Sumpur South Kudus Sijunjung - Nur Azita Amelia Melvi; Asmidar (International Journal For Advanced Research, 2025)
This research is entitled "Plastic Jali-Jali Rope Woven Bag Craft from Mangosteen Fruit Kuntung Sumpur Kudus Selatan Sijunjung". This research method uses a qualitative approach method with observation data collection techniques, literature studies, interviews, and documentation. This study describes the process of making plastic jali-jali rope woven crafts from UMKM kuntung Mangosteen Fruit Sumpur Kudus Selatan Sijunjung to produce a plastic jali-jali rope bag product. Some products produced by UMKM Kuntung Mangosteen Fruit Sumpur Kudus Selatan Sijunjung such as: bags, wallets, and baskets. This product is often used for traditional events, such as baralek, this product is made using one technique, namely the Single weaving pattern technique, thus creating a motif that has aesthetic value.